Carbon sequestration on the subtropical dunes of South Africa: a comparison between native regenerating ecosystems and exotic plantations - Van Aarde, Rudi J. (University of Pretoria, 2013)
Dissertation (MSc (Zoology))--University of Pretoria, 2007.